(untitled) (Scientia Agropecuaria, 2013)
The effect of the dose UV-C irradiation and storage time on the physicochemical, microbiological and antioxidants characteristics of tropical fruits minimally processed was evaluated. The fruits were selected, classified, washed, and cut, which were subjected to immersion in calcium chloride (1% p/v) and ascorbic acid (1% p/v) combined solution for 1 min. Then, the fresh-cut fruits were subjected to doses UV-C irradiation (0. 7 and 14 kJ/m2 ). Finally, samples were packed in trays of polystyrene and covered with polyvinyl chloride film microperforated, and stored at 5 °C with relative humidity of 85 - 90%, during 15 days. Every five days, weight loss, color, soluble solids, firmness, count viable aerobic mesophilic bacteria, fungi and yeasts, total phenolic content, and total flavonoids were evaluated. The significant effect of the dose UV-C irradiation and storage time on the physicochemical, microbiological, and antioxidants characteristics evaluated in tropical fruits minimally processed was significant (p < 0.05). The dose of UV-C irradiation 7 kJ/m2 yielded the best physicochemical characteristics in mango and mamey, while the dose 14 kJ/m2 was in pineapple. The highest antioxidants characteristics and lowest microbiological count was obtained with the dose of UV-C irradiation 14 kJ/m2 during storage.